Joulu lähellä - sydämessä - Tuulantei; Heikkilä, Hilkka; Aihos, Sirkku; Karhu, Kaisa; Karjalainen, Minna; Kristola, Anna-Mari; Kuivanen, Ritva; Lajunen, Johanna; Lempinen, Leila-Katri; Nevantaus, Auli; Nykänen, Terhi; Sulkakoski, Varpu; et al. (Vaput, 2016)
15 kappaletta.